2023
DOI: 10.3390/ijerph20054485
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Is a Family Affair—Systematic Review and Meta-Analysis on the Associations between Mental Health Problems in Parents and Children during the COVID-19 Pandemic

Abstract: As a multidimensional and universal stressor, the COVID-19 pandemic negatively affected the mental health of children, adolescents, and adults worldwide. In particular, families faced numerous restrictions and challenges. From the literature, it is well known that parental mental health problems and child mental health outcomes are associated. Hence, this review aims to summarize the current research on the associations of parental mental health symptoms and child mental health outcomes during the COVID-19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 147 publications
2
10
0
Order By: Relevance
“…Confirming our hypothesis, we found parents with a mental illness to report higher levels of PS than parents without a mental illness. This is in line with previous studies on parents with depression and anxiety symptoms ( 30 , 33 35 , 70 74 , 88 ). Taking a closer look at the questionnaire’s scales, we found parents with a mental illness to perceive less social support and less support in parental relationship.…”
Section: Discussionsupporting
confidence: 93%
“…Confirming our hypothesis, we found parents with a mental illness to report higher levels of PS than parents without a mental illness. This is in line with previous studies on parents with depression and anxiety symptoms ( 30 , 33 35 , 70 74 , 88 ). Taking a closer look at the questionnaire’s scales, we found parents with a mental illness to perceive less social support and less support in parental relationship.…”
Section: Discussionsupporting
confidence: 93%
“…However, young people were deeply affected by the restrictive measures imposed globally to reduce transmission, such as quarantine, lockdown, and social distancing, often referred to as Non-Pharmaceutical Interventions (NPIs), which considerably changed their daily lives ( 3 ). They were confined at home for long periods, with limited opportunity for learning and reduced peer contact, together with adults who were often anxious or psychologically stressed by the circumstances, which added to their own discomfort ( 3 , 4 ). School closure, enforced in many countries with different durations, was particularly relevant for these age groups, as school is where children and adolescents spend most of their time, and have opportunity for both social interactions and intellectual stimulation ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Children from families with lower socio-economic status were more likely to suffer from mental illness than those from families with higher status. Similarly, a study conducted in Norway (Kinge et al, 2021), a systematic review conducted in low- and middle-income countries (Ribeiro et al, 2023), and a systematic review conducted during the COVID-19 pandemic (Stracke et al, 2023) all found that children’s mental health was related to their parents' socio-economic status. This could be because a low socio-economic status causes social stress and stigma, both of which contribute to poor mental health.…”
Section: Discussionmentioning
confidence: 99%